Maximising intraosseous flow rates: an in-vitro study. (2nd November 2019) - Fenwick, Robert; Nutbeam, Tim; Lowther, Ashleigh; Mann, Tom
Abstract : Background: Attaching a different or using no extension set with intraosseous (IO) needles may affect the time taken to administer fluid. An in-vitro study measured this effect. Methodology: Three methods of administration were examined (10 experiments for each approach): a fluid-giving set directly placed in the IO needle hub (direct-to-hub: DTH); a fluid-giving set connected to the EZ-IO device extension set (EZ set: EZS); and a fluid-giving set connected to a simple three-way extension set (three-way set: TWS). Results: Mean times for administration were 317 s for DTH (SD=15 s), 322 s for TWS (SD=8 s) and 361 s for EZS (SD=19 s). This demonstrated a significant difference between the three groups (ANOVA significance p <0.0001). Conclusion: It may be possible for clinicians to increase IO flow rates by removing or replacing the extension set that is supplied with the EZ-IO needle set.